Gastric Adenocarcinoma in the Setting of IPEX Syndrome. (28th June 2021) - Steffin, David; Bhar, Saleh; Fishman, Douglas S.; Rider, Nicholas L.; Naik-Mathuria, Bindi; Martinez, Caridad; Venkatramani, Rajkumar
Abstract : Immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome is a rare X-linked disorder caused by a loss of function mutation in the FOXP3 gene. It manifests early in infancy with clinical symptoms including autoimmune enteropathy, type 1 diabetes mellitus, and eczema. While aberrant FOXP3 expression has been associated with several types of cancer, little is known regarding the risk of cancer in patients with IPEX harboring the characteristic FOXP3 mutation. Here, we present a unique case of a primary signet ring gastric adenocarcinoma in a pediatric patient with IPEX syndrome.